2022
DOI: 10.1021/acs.organomet.2c00015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzofused O- and N-Heterocycles through Cascade Carbopalladation/Cross-Alkylation of Alkynes Involving the C–C Cleavage of Cyclobutanols

Abstract: We report a Pd-catalyzed route to heterocycles bearing a tetrasubstituted alkene fragment. Our approach merges the intramolecular carbopalladation of tethered alkynes with an alkylation step produced by the C–C cleavage of cyclobutanol derivatives. An alkenyl-Pd(II) intermediate has been isolated and characterized by X-ray diffraction studies. Interestingly, the nature of the tethering alkynyl chain influences the E / Z stereochemistry of the alkenyl fragment in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…In every TM-catalyzed process, the activity of a catalyst and the proper chemoselectivity of the transformation can be extraordinarily affected by the ancillary ligands, which may enable the tuning of a reaction’s outcome. This is the case of widely used phosphine ligands, which are commercially available scaffolds exhibiting significant variation on their electronic and steric properties. , For instance, bulky biaryl-monophosphine ligands are able to promote unique reactivity patterns, especially in Pd-catalyzed cross-coupling reactions, assisting the activation or the formation of C–heteroatom bonds. During the course of our previous studies on processes involving Pd-catalyzed C–C bond cleavage of cyclobutanols and their application to organic synthesis, we observed that the use of a bulky phosphine ligand such as (2-biphenyl)­di- tert -butylphosphine, known as JohnPhos, not only failed to deliver the expected coupling products in good yields but also produced the degradation of the starting cyclobutanol reagent. Intrigued by this observation, we decided to further investigate this curious behavior involving a 2-fold Csp 3 –Csp 3 bond cleavage (Scheme , c), the main features of which are discussed in the present manuscript.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In every TM-catalyzed process, the activity of a catalyst and the proper chemoselectivity of the transformation can be extraordinarily affected by the ancillary ligands, which may enable the tuning of a reaction’s outcome. This is the case of widely used phosphine ligands, which are commercially available scaffolds exhibiting significant variation on their electronic and steric properties. , For instance, bulky biaryl-monophosphine ligands are able to promote unique reactivity patterns, especially in Pd-catalyzed cross-coupling reactions, assisting the activation or the formation of C–heteroatom bonds. During the course of our previous studies on processes involving Pd-catalyzed C–C bond cleavage of cyclobutanols and their application to organic synthesis, we observed that the use of a bulky phosphine ligand such as (2-biphenyl)­di- tert -butylphosphine, known as JohnPhos, not only failed to deliver the expected coupling products in good yields but also produced the degradation of the starting cyclobutanol reagent. Intrigued by this observation, we decided to further investigate this curious behavior involving a 2-fold Csp 3 –Csp 3 bond cleavage (Scheme , c), the main features of which are discussed in the present manuscript.…”
Section: Introductionmentioning
confidence: 99%
“… 26 , 27 For instance, bulky biaryl-monophosphine ligands are able to promote unique reactivity patterns, especially in Pd-catalyzed cross-coupling reactions, assisting the activation or the formation of C–heteroatom bonds. 28 31 During the course of our previous studies on processes involving Pd-catalyzed C–C bond cleavage of cyclobutanols and their application to organic synthesis, 32 we observed that the use of a bulky phosphine ligand such as (2-biphenyl)di- tert -butylphosphine, known as JohnPhos, not only failed to deliver the expected coupling products in good yields but also produced the degradation of the starting cyclobutanol reagent. Intrigued by this observation, we decided to further investigate this curious behavior involving a 2-fold Csp 3 –Csp 3 bond cleavage ( Scheme 1 , c), the main features of which are discussed in the present manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Strained cycloalkanols have been successfully incorporated into synthetic routes involving C–C cleavage, given their ability to coordinate to transition metals and generate σ-alkyl organometallic intermediates upon a β-C elimination step. These last species can undergo further coupling processes depending on the reaction conditions. While they have been widely used for small molecule functionalization, there is only one reported application for the synthesis of polymeric materials. It relates the obtention of a polythiophene chain from a thiophene derivative of 9-fluorenol .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group and the García-López group further developed the palladium-catalyzed cyclization/ring-opening coupling reaction of alkynyl aryl iodide with cyclobutanols (Scheme 1b). 7 Despite these significant achievements, it is also highly desirable to develop a new palladium-catalyzed cyclization of alkynyl aryl iodide to further meet the diverse requirements of synthetic organic chemistry.…”
Section: Introductionmentioning
confidence: 99%